Molecular cytogenetic characterization of isolated recurrent 4q35.2 microduplication in Chinese population: a seven-year single-center retrospective study - Zhuang, Jianlong; Wei, Qiulan; Jiang, Yuying; Zeng, Shuhong; Lou, Haijuan; Zhang, Na; Chen, Chunnuan (BMC pregnancy and childbirth, 2024)
Background With the extensive use of chromosomal microarray analysis (CMA), an increasing number of variants of uncertain significance (VOUS) have been detected. The objective of the present study was to elucidate the pathogenicity and clinical variability associated with isolated recurrent 4q35.2 microduplications within the Chinese population. Methods The present study involved 14 cases of isolated recurrent 4q35.2 microduplication (including 12 fetuses and 2 cases of pediatric patients) out of 5,188 subjects who sought genetic consultation at our hospital and received CMA detection. WES technology was subsequently utilized to identify additional sequence variants in a patient with multiple clinical anomalies. Results All 14 cases exhibited isolated recurrent 4q35.2 microduplications spanning a 1.0-Mb region encompassing the ZFP42 gene. Among the 12 fetuses, 11 displayed normal clinical features, while one was born with renal duplication and hydronephrosis. Additionally, in the two pediatric patients, WES was performed for Case 1, who presented with congenital cataracts, severe intellectual disability, and seizures. This patient inherited the 4q35.2 microduplication from his phenotypically normal mother. WES identified a novel NM_000276:c.2042G > T (p.G681V) variant in the OCRL gene, which is associated with Lowe syndrome and may account for the observed phenotypic variability within this family. Conclusion A series of 14 cases with isolated recurrent 4q35.2 microduplications were investigated, highlighting a potential association with increased susceptibility to renal abnormalities. Further, the present findings may expand the mutation spectrum of the OCRL gene associated with Lowe syndrome and provide valuable insights for the genetic etiological diagnosis of patients with unexplained copy number variants.